2016
DOI: 10.1080/2162402x.2015.1127493
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD245 as myosin 18A, a receptor for surfactant A: A novel pathway for activating human NK lymphocytes

Abstract: CD245 is a human surface antigen expressed on peripheral blood lymphocytes, initially delineated by two monoclonal antibodies DY12 and DY35. Until now, CD245 molecular and functional characteristics remained largely unknown. We combined immunological and proteomic approaches and identified CD245 as the unconventional myosin 18A, a highly conserved motor enzyme reported as a receptor for the surfactant protein A (SP-A), that plays a critical role in cytoskeleton organization and Golgi budding. We report that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Emerging evidence indicated that resting NK cell functional priming is stringently controlled by the integration of various immune modulators [10]. Recent studies demonstrated that SP-D could bind to NK cells and modulate their function [36,37]. Additionally, a previous study found that ficolin-1 could attach to the NK cell surface via the pathogen recognition domain of ficolin-1, although whether this interaction might affect NK cell function was still unclear [38].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Emerging evidence indicated that resting NK cell functional priming is stringently controlled by the integration of various immune modulators [10]. Recent studies demonstrated that SP-D could bind to NK cells and modulate their function [36,37]. Additionally, a previous study found that ficolin-1 could attach to the NK cell surface via the pathogen recognition domain of ficolin-1, although whether this interaction might affect NK cell function was still unclear [38].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Additionally, the interaction between myosin-18A and SP-A was also found to be important for macrophage activation ( Yang et al, 2015 ). Besides, CD245, a highly conserved motor enzyme reported as a receptor for SP-A, has also been identified as myosin-18A ( De Masson et al, 2016 ). Certainly, these studies shed light on the new feature of myosin-18A function.…”
Section: Introductionmentioning
confidence: 99%
“…S6C) aMϕs. Myo18A is an unconventional myosin that does not operate as a traditional molecular motor, having both intracellular and cell-surface locations (14), and was recently defined as CD245 (15). Immune activation results in Myo18A localization on the cell surface, where it binds to the collagen-like domain of SP-A (6, 16) and we confirmed that an intact collagen-like domain is required to enhance IL-4-mediated type 2 responses (Fig.…”
mentioning
confidence: 99%